Aspect and reference time - Borik, Olga, 1972- (Oxford studies in theoretical linguistics, 2006)
Investigating the temporal structure of language, this text deals with issues in the understanding of tense and aspect proposes a new approach to the main problems in the area, and seeks to establish the universal semantic properties of two important and contentious aspectual categories, perfectivity and imperfectivity.